Mortality risk factors among non-ICU patients with nosocomial vascular catheter-related bloodstream infections: a prospective cohort study. Issue 1 (May 2018) - Saliba, P.; Hornero, A.; Cuervo, G.; Grau, I.; Jimenez, E.; García, D.; Tubau, F.; Martínez-Sánchez, J.M.; Carratalà, J.; Pujol, M.
Summary: Background: Vascular catheter-related bloodstream infections (CRBSIs) are highly preventable hospital-acquired infections and a major threat to patient safety. While there is significant information regarding CRBSI outcome among intensive care unit (ICU) patients, data regarding non-ICU patients are scarce. Aim: To determine the risk factors associated with 30-day mortality among non-ICU patients with nosocomial CRBSIs. Methods: Prospective cohort study of non-ICU patients with nosocomial CRBSIs in a tertiary care centre between January 2004 and December 2014. The primary outcome was 30-day mortality, defined as death from any cause within 30 days of CRBSI. Follow-up was performed 30 days after CRBSI onset. Time until death was the dependent variable in Cox regression analysis. Findings: In total, 546 cases of CRBSI were identified. The mean age of patients was 64.5 years [interquartile range (IQR) 55–75 years], 66% were male, and the mean Charlson score was 3.59 (IQR 2–5). Of the 546 cases, 58.4% resulted from central venous catheters and 41.6% from peripheral venous catheters. The causative agents were Gram-positive cocci (70.1% of cases), Gram-negative bacilli (31.1%) and Candida spp. (1%). Mortality within 30 days was 13.9%, with no significant changes over the study period. Independent risk factors for 30-day mortality were Charlson score ≥4 [hazard ratio (HR) 1.80, 95% confidence interval (CI) 1.19–2.73], Staphylococcus aureus infection (HR 2.67, 95% CI 1.61–4.43) and  Candida spp. infection (HR 6.1, 95% CI 2.08–18.04). Age; area of admission; type, use and site of vascular catheter; and administration of appropriate empirical antibiotic treatment were not independent risk factors for 30-day mortality. Conclusion: Nosocomial CRBSIs outside ICUs are associated with high risk of mortality, particularly among patients with a higher Charlson score and bloodstream infections caused by Staphylococcus aureus and Candida spp.